2013
DOI: 10.5897/jssem2013.0380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different land use systems on selected soil properties in South Ethiopia

Abstract: A study was conducted to determine the effect of different land use systems on soil physical and chemical properties in Sodo Zuria Woreda of Wolaita zone Southern Ethiopia. Differences in soil properties in different land use types at two depths (0-15 and 15-30 cm) were observed on many soil properties important to crop growth. Enset (Ensete Ventricosum) fields had higher pH, electrical conductivity (EC), available P and Zn, exchangeable Ca and K which is attributed due to the addition of manure, whereas maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 13 publications
16
56
1
Order By: Relevance
“…This may be explained by the fact that salinity caused by natural factors is strictly local and that its main sources are anthropogenic, i.e., mineral fertilizers. Similar results were published by other authors [35][36], who also demonstrated a significant effect of land use on selected physical and chemical properties of soils in the investigated areas. Moreover, soil properties are commonly used in the analysis of the impact of selected factors on soil quality [37][38][39][40][41][42][43][44][45].…”
Section: Impact Of Land Use On Soil Propertiessupporting
confidence: 80%
“…This may be explained by the fact that salinity caused by natural factors is strictly local and that its main sources are anthropogenic, i.e., mineral fertilizers. Similar results were published by other authors [35][36], who also demonstrated a significant effect of land use on selected physical and chemical properties of soils in the investigated areas. Moreover, soil properties are commonly used in the analysis of the impact of selected factors on soil quality [37][38][39][40][41][42][43][44][45].…”
Section: Impact Of Land Use On Soil Propertiessupporting
confidence: 80%
“…We found that national level policies, extreme climatic events, biotic stress, population increase (due to the combined effects of migration and natural increase), and urban expansion were major drivers of farming systems changes in the Hawassa area. At the local level, population growth, the expansion of urban areas, the biophysical conditions found in each district (in particular soil fertility (Kiflu & Beyene, 2013;Mellisse, Descheemaeker, Giller, Abebe, & van de Ven, 2018)) and the distance to markets influenced land cover/land use changes and farming systems. Per capita land and livestock numbers decreased for the three districts leading 1984, 1998, and 2014. to variable responses in farmers' livelihood strategies.…”
Section: Discussionmentioning
confidence: 99%
“…() found higher SOC stock in the home garden than sugarcane plantation in Ethiopia. In contrast, in the southern Ethiopia, Kiflu and Beyene () found similar SOC content in the home garden and cropland. In our study area, the organic matter input in the home garden includes manure and household refuse ( Laekemariam , ) as well as litter input from the perennial crops.…”
Section: Discussionmentioning
confidence: 92%
“…The SOC in the Eucalyptus woodlot and grazing lands did not differ from the home garden. SOC in the home garden was not different from Eucalyptus woodlot (Duguma et al, 2010), while the home garden had lower SOC content than smallholding grazing land (Kiflu and Beyene, 2013). Few studies investigated the influence of home garden on soil properties as compared with Eucalyptus woodlot or grazing land.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation